Snow cover in Hawai'i (1893–1953) and its effect on ground temperature. Issue 1 (1st January 2019) - Martin, Jake; Schorghofer, Norbert; Yoshikawa, Kenji; Klasner, Frederick L.
ABSTRACT: Snow occasionally falls on the highest mountains of tropical Hawaiʻi: Maunakea, Maunaloa, Haleakalā, and Hualālai. We digitized and analyzed monthly Weather Bureau records of snow in Hawaiʻi from 1893 to 1972. In the half-century 1901–1950, Maunakea had an estimated average of one month of snow cover per year. Snow was especially abundant from 1922 to 1940, but was relatively rare from 1908 to 1921. Snow cover may play a role in the formation and preservation of permafrost. MODIS satellite data are used to measure the albedo of the snow surface as a function of its age. Following winters with snow, the ground temperature at 1 m depth is lower than after a winter without significant snow cover, and hence snow cover favors permafrost conditions.